Exploring non-coding RNA mechanisms in hepatocellular carcinoma: implications for therapy and prognosis - Tian, Yu; Zhang, Meng; Liu, Li-xia; Wang, Zi-chao; Liu, Bin; Huang, Youcai; Wang, Xiaoling; Ling, Yun-zhi; Wang, Furong; Feng, Xiaoqiang; Tu, Yanyang (Frontiers in Immunology, 2024)
Hepatocellular carcinoma (HCC) is a significant contributor to cancer-related deaths in the world. The development and progression of HCC are closely correlated with the abnormal regulation of non-coding RNAs (ncRNAs), like microRNAs (miRNAs), long non-coding RNAs (lncRNAs), and circular RNAs (circRNAs). Important biological pathways in cancer biology, such as cell proliferation, death, and metastasis, are impacted by these ncRNAs, which modulate gene expression. The abnormal expression of non-coding RNAs in HCC raises the possibility that they could be applied as new biomarkers for diagnosis, prognosis, and treatment targets. Furthermore, by controlling the expression of cancer-related genes, miRNAs can function as either tumor suppressors or oncogenes. On the other hand, lncRNAs play a role in the advancement of cancer by interacting with other molecules within the cell, which in turn affects processes such as chromatin remodeling, transcription, and posttranscriptional processes. The importance of ncRNA-driven regulatory systems in HCC is being highlighted by current research, which sheds light on tumor behavior and therapy response. This research highlights the great potential of non-coding RNAs (ncRNAs) to improve patient outcomes in this difficult disease landscape by augmenting the present methods of HCC care through the use of precision medicine approaches.